Gomphidae of Guangdong & Hong Kong, China (Odonata: Anisoptera) - Wilson, Keith Duncan Peter; Xu, Zaifu (Zootaxa, 2009)
Guangdong is located in south China, which is recognized as a global centre of biodiversity for Gomphidae. Taxonomic and faunistic information is provided for 24 poorly known species of Gomphidae from Guangdong and Hong Kong. A total of 50 gomphid species belonging to 25 genera are enumerated, including 12 newly recorded from Guangdong and one newly recorded from Hong Kong. Four species are synonymised, one subspecies is promoted to species status and new generic combinations are provided for two species. The synonyms comprise: Lamelligomphus jiuquensis Liu 1993 = Lamelligomphus formosanus (Oguma 1926), Lamelligomphus parvulus Zhou and Li 2000 = Lamelligomphus laetus Yang and Davies 1993, Melligomphus moluami Wilson 1995 = Ophiogomphus guandongensis Chao 1994 and Phaeandrogomphus chaoi Zhu & Liang 1994 = Phaenandrogomphus tonkinicus (Fraser 1926). The subspecies Leptogomphus elegans hongkongensis Asahina 1988 is elevated to species status, viz Leptogomphus hongkongensis. Ophiogomphus guandongensis is transferred to Melligomphus Chao 1990 and Nihonogomphus indicus Lahiri 1987 is transferred to Orientogomphus Chao 1990. Keys are provided for the identification of Chinese Lamelligomphus Fraser and all known species of Nihonogomphus Oguma.